Analisis Budaya Organisasi, Motivasi, Pelatihan dan Kemampuan Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Dinas Pengendalian Penduduk Dan Keluarga Berencana (DPPKB) Kabupaten Labuhanbatu Utara - Putri Piliang, Asdevi Habibi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the influence of Organizational Culture, motivation, training and work ability on employee job satisfaction at the Office of Population Control and Family Planning (Dppkb) North Labuhanbatu. The sample in this study 39 respondents using SPSS 22.0. The results showed that organizational culture, motivation, training and work ability affect partially and simultaneously on job satisfaction at the Office of Population Control and Family Planning (Dppkb) North Labuhanbatu. From the results of data processing on the T test (partial) the value of the count for organizational culture variable (1.367) with a significant value of 0.177, motivation of (3.714) with a significant value of 0.000, training of (1.283) with a significant value of 0.245, the ability of (6.543) with a significant value of 0.000, while the value of the table 33 to obtain the value of 1692 ttable. Thus the hypothesis is accepted. Â From the results of data processing on the test F (simultaneous) DF obtained by Count (k-1) = (5-1) = 4 while DF2 obtained calculation (n-k) = (39-5-1) = 33 with a = 5% so the value of Ftable = 2.66 the value of F count > F table = 25,137 > 2.66 with a significant value of 0.000 < 0.05 thus simultaneously organizational culture, motivation, training and ability have a significant labuhanbatu North. Thus the hypothesis is accepted.